Ciliopathy-associated missense mutations in IFT140 are tolerated by the inherent resilience of the IFT machinery - Beyer, Tina; Diwan, Gaurav; Leonhard, Tobias; Dahlke, Katrin; Klose, Franziska; Stehle, Isabel F.; Seda, Marian; Bolz, Sylvia; Woerz, Franziska; Russell, Robert B.; Jenkins, Dagan; Ueffing, Marius; et al. (Molecular & cellular proteomics, 2025)
Genotype-phenotype correlations of rare diseases are complicated by low patient number, high phenotype variability, and compound heterozygosity. Mutations may cause instability of single proteins, and affect protein complex formation or overall robustness of a specific process in a given cell. Ciliopathies offer an interesting case for studying genotype-phenotype correlations as they have a spectrum of severity and include diverse phenotypes depending on different mutations in the same protein. For instance, mutations in the intraflagellar transport protein IFT140 cause a vast spectrum of ciliopathies ranging from isolated retinal dystrophy to severe skeletal abnormalities and multi-organ diseases such as Mainzer-Saldino and Jeune syndrome. Here, the quantitative effects of 23 missense mutations in IFT140, which forms part of the crucial IFT-A complex of the ciliary machinery, were analyzed using affinity purification coupled with mass spectrometry (AP-MS). A subset of 10 mutations led to a significant and domain-specific reduction in IFT140-IFT-A complex interaction indicating complex formation issues and potentially hampering its molecular function. Knockout of IFT140 led to loss of cilia, as shown before. However, phenotypically only mild effects concerning cilia assembly were observed for two out of four tested IFT140 missense mutations. Therefore, our results demonstrate the utility of AP-MS in discerning pathogenic MMs from polymorphisms, and we postulate that reduced function is tolerated by the evolutionarily highly conserved IFT-A system.
Gesehen am 28.07.2025
Online verfügbar 27 January 2025, Version des Artikels 24 February 2025